Presence of extraintestinal pathogenic Escherichia coli in butcheries in Taquaritinga, SP, Brazil - Santo, Edilene; Rodolpho, Daniela; Marin, José Moacir (FapUNIFESP (SciELO), 2007)
The study was conducted in twenty-three butcheries in the city of Taquaritinga, State of São Paulo, Brazil, surveyed during a 10 months period. Among two hundred and eighty-seven Escherichia coli strains isolated from samples of ground beef, meat-grinding-machines and the hands of manipulators, five were recognized as extraintestinal pathogenic E. coli (ExPEC), showing virulence factors (P and S fimbriae, hemolysin and aerobactin) and presenting multidrug resistance. Retail-sold food may constitute an important vehicle for the dissemination of ExPEC in communities, giving rise to reasons for concern.
Keywords: Butchery; Escherichia coli; ExPEC; Ground beef